Location matters: Overlooked ethnic‐geographic effect in China and Austria on propofol/cisatracurium sex differences among a population pharmacokinetic/pharmacodynamic (PopPK/PD) covariate analysis in men, women, and one transgender subject - Dahaba, Ashraf A.; Xiao, Zhaoyang; Zhu, Xiaoling; Oettl, Karl; Dong, Hailong; Xiong, Lize; Zelzer, Sieglinde; Zhao, Shuiyu; Reibnegger, Gilbert (Fundamental & clinical pharmacology, 2022)
A quick literature search using “sex/gender” vs. the commonly used hypnotic propofol or neuromuscular‐blocking agent cisatracurium will reveal numerous contradictory sex difference publications depending on the ethnic‐geographic location of where these studies were conducted. We induced anesthesia with cisatracurium besylate (GlaxoSmithKline) 100 μg kg−1 administered exactly 1 minute following propofol (AstraZeneca) 2 mg kg−1. In 20 male and 20 female ethnic Han‐Chinese test set patients (Xi'an China), and in similar ethnic white Austrian validation set patients (Graz Austria), we quantified propofol/cisatracurium pharmacodynamic parameters namely propofol onset time, lag time, plasma concentrations (Cp) at loss‐of‐behavioral response (LOBR) using bispectral index (BIS); cisatracurium onset time, lag time, and Cp at T1% (first twitch of train‐of‐four) complete twitch suppression using mechanomyography (MMG). Serial arterial blood samples were collected for population pharmacokinetic (PopPK) analysis of all demographic and biological covariates (region, sex, age, weight, and height) versus volumes of distribution and clearances pharmacokinetic parameters. In Chinese women (but not in white women), propofol Cp at LOBR was 33.60% lower than men and cisatracurium Cp at T1% complete twitch suppression was 21.49% lower than men, a clear pharmacodynamic assertion. Region and weight were significant PopPK covariates. We demonstrated that sex differences are influenced by ethnic‐geographic location as only in Chinese women (but not in white women) propofol Cp at LOBR and cisatracurium Cp at T1% complete twitch suppression were lower than in men. When defining sex differences, ethnic‐geographic location should be taken into consideration as a predictive factor for optimizing propofol/cisatracurium initial loading recommended dosages.